Solution of secure multi-party multi-data raking problem based on El Gamal encryption - LIU Wen1; LUO Shou-shan2; CHEN Ping4 (Tongxin xuebao)
Based on El Gamal homomorphic encryption,a protocol of secure multi-party multi-data ranking problem was proposed.The problem extended millionaires’ problem.Furthermore,the correctness and security of this protocol were shown in semi-honest model,using the definition of secure multi-party computation.The solution of secure multi-party multi-data ranking problem can form a fundamental basis of new-style electronic transaction,such as private biding and auction,secret online transaction and so on.